2015
DOI: 10.1039/c5cc01716e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of enantioenriched 1,2-trans-diamines using the borono-Mannich reaction with N-protected α-amino aldehydes

Abstract: The three-component Petasis borono-Mannich reaction starting with easily accessible N-protected α-amino aldehydes produces efficiently and diastereoselectively 1,2-trans-diamines with an enantiomeric excess of up to 98%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…of 2 and 7a in CH 2 Cl 2 at 120 °C for 30 min under microwave (MW) radiation or at 50 °C for 36 h by conventional heating (Table , Entries 1 and 2). In both cases, the reaction produced the desired compound 11 in yields of 85 and 52 %, respectively, but with low ee values (30 to 42 %) , . The X‐ray crystal diffraction, analysis of 11 confirmed that the reaction occurred with a high degree of diastereocontrol and led exclusively to the anti adduct.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…of 2 and 7a in CH 2 Cl 2 at 120 °C for 30 min under microwave (MW) radiation or at 50 °C for 36 h by conventional heating (Table , Entries 1 and 2). In both cases, the reaction produced the desired compound 11 in yields of 85 and 52 %, respectively, but with low ee values (30 to 42 %) , . The X‐ray crystal diffraction, analysis of 11 confirmed that the reaction occurred with a high degree of diastereocontrol and led exclusively to the anti adduct.…”
Section: Resultsmentioning
confidence: 94%
“…Yield of the crude aldehyde. For the details of reagents and conditions, see the Supporting Information or ref …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Ozonolysis of 3d gave acyl cyanide, [15] which was directly converted into amino acid methyl ester 7 using MeOH and Et 3 N. [16] Ther eduction of 7 with LiBH 4 afforded amino alcohol 8, [17] which was cyclized to oxazolidinone 9. [14] Ozonolysis of 3d gave acyl cyanide, [15] which was directly converted into amino acid methyl ester 7 using MeOH and Et 3 N. [16] Ther eduction of 7 with LiBH 4 afforded amino alcohol 8, [17] which was cyclized to oxazolidinone 9.…”
Section: Methodsmentioning
confidence: 99%
“…Zuschriften the coupling-cyclization of 3d with allyl bromide,a nd afforded product 6 in moderate yield without racemization (Scheme 2b). [14] Ozonolysis of 3d gave acyl cyanide, [15] which was directly converted into amino acid methyl ester 7 using MeOH and Et 3 N. [16] Ther eduction of 7 with LiBH 4 afforded amino alcohol 8, [17] which was cyclized to oxazolidinone 9. [18] Cleavage of the SES group from 9 using TBAF gave 10 without any loss of enantiopurity (Scheme 2c).…”
Section: Angewandte Chemiementioning
confidence: 99%